2017
DOI: 10.1139/cjss-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Direct chemical speciation of soil phosphorus in a Saskatchewan Chernozem after long and short-term manure amendments

Abstract: Chemical form of phosphorus (P) in soils influences both plant accessibility and solute transport of P. Soil P speciation receiving inorganic and organic fertilizers is extensively studied to address a range of agronomic and environmental concerns. It is known inorganic P sources react over long time scales in soils, but relatively few studies have focused upon long-term P speciation changes in soils receiving organic amendments. This study was conducted to address this gap by providing detailed information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 57 publications
5
25
0
Order By: Relevance
“…The LCF results suggested the adsorption of P to mineral phases of Fe, organic P, and Ca phases (in some of the RF samples). These results were in line with other studies [26,31,33] that observed a dominance of adsorbed P in manure amended soils and highlighted the role of Fe in the chemistry of P in manure amended soils. In the DS, the marginal shift in the dominant P species in AT0, from 64.9% adsorbed P and 35.1% organic P (Table 3, Figure 6b) before planting to 63.9% adsorbed P and 33.1% organic P, and the occurrence of apatite P (2.9%) after harvest (Table 3, Figure 6a) were also accompanied by a reduction in the pH and total and available P after harvest (Table 3, Figure 5a,b).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The LCF results suggested the adsorption of P to mineral phases of Fe, organic P, and Ca phases (in some of the RF samples). These results were in line with other studies [26,31,33] that observed a dominance of adsorbed P in manure amended soils and highlighted the role of Fe in the chemistry of P in manure amended soils. In the DS, the marginal shift in the dominant P species in AT0, from 64.9% adsorbed P and 35.1% organic P (Table 3, Figure 6b) before planting to 63.9% adsorbed P and 33.1% organic P, and the occurrence of apatite P (2.9%) after harvest (Table 3, Figure 6a) were also accompanied by a reduction in the pH and total and available P after harvest (Table 3, Figure 5a,b).…”
Section: Discussionsupporting
confidence: 92%
“…The application of manure to agricultural soils is beneficial in many ways: it provides essential macronutrients such as N and P [19][20][21][22], improves soil organic matter content [23], and helps to maintain soil quality [24]. However, manures can also alter the physical and chemical properties of the soil [25], with P minerals in the soil transforming into new phases even after short term manure application [26], and pose an environmental threat to surface waters if not properly managed. The bioavailability of P in manure and manure amended soils varies with the type of manure and soil, the solubility of the P compounds in them, and the reaction products formed upon their application [20,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were processed and analyzed with the Athena software package (Ravel and Newville, 2005). Linear combination fitting (LCF) was performed on adsorption samples with a large library of high quality phosphate reference compounds that included adsorbed phosphate, phosphate minerals with a range of cations, and organic phosphates (Kar et al, 2017; Hamilton et al, 2018). Standards were diluted in boron nitride to avoid saturation effects on XANES from self‐absorption.…”
Section: Methodsmentioning
confidence: 99%
“…In soil systems, Nuclear Magnetic Resonance, X-Ray Diffraction, and infrared techniques all have significant issues due to the need for sample extraction to overcome matrix effects and also due to low concentration of P within soils [18]. Phosphorus K-edge X-ray absorption near edge spectroscopy (XANES) is an established technique [19][20][21][22] for direct solid-state P speciation in soils that has matured as the accessibility of suitable synchrotron radiation sources and beamlines has increased [23][24][25][26]. However, the utility of P XANES spectroscopy is limited in many cases by the breadth and quality of spectral reference libraries that are used in semi-quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%